2010
DOI: 10.1002/ejoc.201001110
|View full text |Cite
|
Sign up to set email alerts
|

Racemic and Optically Pure Heptahelicene‐2‐carboxylic Acid: Its Synthesis and Self‐Assembly into Nanowire‐Like Aggregates

Abstract: Keywords: Arenes / Alkynes / Cyclotrimerisation / Nanostructures / Scanning probe microscopy Heptahelicene-2-carboxylic acid was effectively synthesised from suitably functionalised naphthalene building blocks. Methoxy-substituted 1,1Ј-ethyne-1,2-diylbis(2-but-3-yn-1-ylnaphthalene) was cyclised in the presence of CpCo(CO) 2 / PPh 3 to 2-methoxy-7,8,11,12-tetrahydroheptahelicene, which was converted into heptahelicen-2-yl trifluoromethanesulfonate. This reactive intermediate underwent Pd(OAc) 2 / dppp-catalysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 45 publications
(55 reference statements)
0
15
0
Order By: Relevance
“…1D, have been reported: On calcite, Kühnle and coworkers observed islands of enantiopure [7]helicene-2-carboxylic acid and chains of the racemate, both stabilized by π-π stacking. [19][20][21] The present article reports on the chirality transfer which takes place during the self-assembly of enantiopure dicyanohelicene building blocks into 1D chains, a particular focus being put on the influence of the intermolecular bonding motif. With enantiomers of cyano-functionalized helicenes, (P)-(+)-6,13dicyano [7]helicene and (M)-(-)-6,13-dicyano [7]helicene ((P)-1 and (M)-1) ( Fig.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…1D, have been reported: On calcite, Kühnle and coworkers observed islands of enantiopure [7]helicene-2-carboxylic acid and chains of the racemate, both stabilized by π-π stacking. [19][20][21] The present article reports on the chirality transfer which takes place during the self-assembly of enantiopure dicyanohelicene building blocks into 1D chains, a particular focus being put on the influence of the intermolecular bonding motif. With enantiomers of cyano-functionalized helicenes, (P)-(+)-6,13dicyano [7]helicene and (M)-(-)-6,13-dicyano [7]helicene ((P)-1 and (M)-1) ( Fig.…”
Section: Supporting Information Placeholdermentioning
confidence: 99%
“…Furthermore, it has been reported that certain helicenes can self-assemble into homochiral supramolecular columns, which subsequently pack together to form large crystalline structures in both concentrated solution and thin films. [18][19][20] This supramolecular aggregation gives directionality and alignment to the helical electronic system, and can result in a dramatic increase in their chiroptical response 20 and strong enhancement of their nonlinear optical properties 21 .…”
mentioning
confidence: 99%
“…In view of the widespread synthetic activity in the preparation of new types of helicenes, it is remarkable that relatively less appears to have been done with the “grandfather of helicenes”, namely hexahelicene, to provide it with substituents that would allow further manipulation, particularly on surfaces. The synthesis of heptahelicene 2‐carboxylic acid has been described recently by means of cross‐coupling followed by [2+2+2] cyclization .…”
Section: Resultsmentioning
confidence: 99%